Complications Associated With Lateral Interbody Fusion: Nationwide Survey of 2998 Cases During the First 2 Years of Its Use in Japan. Issue 19 (1st October 2017) - Fujibayashi, Shunsuke; Kawakami, Noriaki; Asazuma, Takashi; Ito, Manabu; Mizutani, Jun; Nagashima, Hideki; Nakamura, Masaya; Sairyo, Koichi; Takemasa, Ryuichi; Iwasaki, Motoki
Abstract : Study Design: Retrospective nationwide questionnaire-based survey of complications. Objective: To elucidate the incidence of complications and risk factors associated with lateral interbody fusion (LIF). Summary of Background Data: After its introduction to Japan in February 2013, the numbers of LIF cases have increased substantially because of the advantages of this minimally invasive procedure. However, LIF has the potential risk of several complications unique to the procedure. Although there are many reports of complications, no nationwide survey has been conducted. Methods: Questionnaires were sent to all Japanese Society for Spine Surgery and Related Research (JSSR) members. Questionnaires requested information about surgical procedures (XLIF or OLIF), patient characteristics, preoperative diagnosis, complications, salvage procedures, final outcomes, and the surgeon's experience of LIF. The data from replies received between March 2013 and April 2015 were recorded on a web site and the details of complications were analyzed by a JSSR research team. Results: Seventy-one institutions (12.3%) answered "yes" to LIF experience and 2998 cases (1995 XLIF and 1003 OLIF) were enrolled in this study. The response rate was 86.1%. A total of 540 complications were reported, of which 474 (84.8%) could be further analyzed. The overall complication rate was 18.0%. The most frequent complications were sensory nerve injury (5.1%) and psoas weakness (4.3%) and the majority resolved spontaneously. The rates of major vascular injury, bowel injury, and surgical site infection were 0.03%, 0.03%, and 0.7%, respectively. The overall reoperation rate was 2.2%. Higher rates of sensory nerve injury and psoas weakness were reported for XLIF and higher rates of peritoneal laceration and ureteral injury were reported for OLIF. Conclusion: A nationwide survey of complications associated with LIF was conducted. Although the majority of complications were minor, a relatively high rate of complications was reported. Approach-related specific features of the two procedures were identified. Level of Evidence: 4